PROBLEMS OF ORGANIZING LABORATORY WORK IN PHYSICS LESSONS AND THEIR SOLUTIONS - Jumanov Anvar Alisherovich; Azimova Gulsum Tolibovna; Ibotov Oktamjon Navrozovich (Galaxy International Interdisciplinary Research Journal, 2024)
The article discusses methodological approaches to conducting laboratory work in physics lessons, the role of physical science in choosing the future professional approach of students. The technique of performing laboratory work in physics with research elements of teaching based on a differentiated approach is described. Examples of laboratory work of varying degrees of complexity are given, the effectiveness of which has been debated.